Outdoor Learning With Outbond Variations 21st Century Social Studies Learning Alternative - Maesaroh Maesaroh; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
Social studies learning process has not been implemented optimally. The application of the Outbound variation of the Outdoor Learning method as a solution to this problem . The instrument used was an observation sheet for student creativity and collaboration. The implementation of learning using an outdoor learning strategy with outbound variations is carried out optimally with very good criteria. The application of this method is carried out by inviting students to study outside the classroom (out door learning) to increase student creativity and collaboration in a pleasant learning atmosphere. The outdoor learning approach (outdoor learning) of outbound variations for children is very useful, it is a learning program (training) for children carried out in the open based on the principle of